2021
DOI: 10.1111/jace.17655
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical properties of ultra‐low porous auxetic piezocomposite: from the perspective of Poisson’s ratio

Abstract: In this study, the ultra‐low porous auxetic piezoelectric composite made of lead zirconate titanate (PZT) and hollow polyvinylidine difluoride (PVDF) is first proposed by combining “additive” and “subtractive” approaches. The electromechanical properties of the auxetic piezoelectric composite are investigated by finite element analysis. It is found that the ultra‐low porosity in the composite may lead to great extensibility along with the excellent figures of merit obtained in conventional highly porous piezoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…(3) The electromechanical properties of this piezoelectric composite material were more customizable than traditional porous piezoelectric materials. These findings provided some effective guidance for the design and development of new auxetic piezoelectric metamaterials [83]. A piezoelectric energy harvester combining the two key topologies of auxetic and kirigami was also developed.…”
Section: Piezoelectric Auxetic Sensormentioning
confidence: 90%
“…(3) The electromechanical properties of this piezoelectric composite material were more customizable than traditional porous piezoelectric materials. These findings provided some effective guidance for the design and development of new auxetic piezoelectric metamaterials [83]. A piezoelectric energy harvester combining the two key topologies of auxetic and kirigami was also developed.…”
Section: Piezoelectric Auxetic Sensormentioning
confidence: 90%
“…[ 22 ] Furthermore, Tang et al demonstrated improved piezoelectric properties with an auxetic metamaterial. [ 23,24 ] This is contrary to the fact that the piezoelectric properties are reduced with increasing porosity. It is unclear whether the piezoelectric properties are influenced only by the shape or by the mechanical properties per se.…”
Section: Introductionmentioning
confidence: 86%
“…[22] Furthermore, Tang et al demonstrated improved piezoelectric properties with an auxetic metamaterial. [23,24] This is contrary to the fact that the DOI: 10.1002/adem.202201387…”
Section: Introductionmentioning
confidence: 96%